Optimalisasi Penggunaan Teknologi Digital sebagai Strategi Efektif dalam Meningkatkan Literasi Sains di Sekolah Dasar - Lidia Vistarini (CV. Aksara Global Akademia, 2025)
The low scientific literacy of elementary school students, influenced by the use of conventional learning methods and lack of interactivity, encourages the need for new innovations based on digital technology. This study aims to test the optimization of the use of digital technology as a strategy to improve scientific literacy through a quasi-experimental method with a pretest-posttest control group design. The research subjects consisted of 60 fifth-grade students from one elementary school, namely SDN Pondok Labu 03, taken from 2 classes, each consisting of 30 students (30 students in the experimental group and 30 students in the control group). The experimental group was given a digital technology-based science learning treatment, namely a virtual laboratory (Labster), and an educational application (Quizizz), for 8 weeks, while the control group used conventional methods. The research instruments included a scientific literacy test (HOTS questions) and student activity observation sheets. Data were analyzed quantitatively using t-test and ANOVA to compare the increase in scientific literacy scores between the two groups. The results showed that the experimental group experienced a significant increase in scientific literacy scores (N-Gain 0.72) compared to the control group (N-Gain 0.32). The research conclusion proves that the systematic integration of digital technology is effective in improving the scientific literacy of elementary school students at Pondok Labu 03.